2008
DOI: 10.1007/s11258-008-9446-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural patterns and biodiversity in burned and managed Aleppo pine stands

Abstract: Increasing anthropic pressure is making forest fires more frequent in the Mediterranean Basin and therefore affecting the response of native flora and fauna. Two large fires occurred in summer, 1994, in the Southeastern Iberian Peninsula. Aleppo pine, the main tree species, regenerated naturally after the fire. In this study we are interested in strategies for maximizing Aleppo pine tree recovery and conservation of its ecosystem. We performed thinning and pruning in the pine tree stands 5 and 10 years after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 37 publications
3
19
0
3
Order By: Relevance
“…This preventive approach may be crucial in Aleppo pine forests, as they usually have a low crown height (3-6.5 m) which increases the risk of crown fire initiation even under moderate burning conditions (Mitsopoulos and Dimitrakopoulos, 2007). However, differences in TD3 among thinning regimes were not very notable, as other authors have also reported (Moya et al, 2009). TD3 decreased with time in all cases, in agreement with previous references (Crecente-Campo et al, 2009), but the decrease we observed was greater in heavier thinnings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This preventive approach may be crucial in Aleppo pine forests, as they usually have a low crown height (3-6.5 m) which increases the risk of crown fire initiation even under moderate burning conditions (Mitsopoulos and Dimitrakopoulos, 2007). However, differences in TD3 among thinning regimes were not very notable, as other authors have also reported (Moya et al, 2009). TD3 decreased with time in all cases, in agreement with previous references (Crecente-Campo et al, 2009), but the decrease we observed was greater in heavier thinnings.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, in a long-term thinning experiment in northeast China, thinning from below was found to produce some departures from the random distribution of trees observed in control plots (Lei et al, 2007). In a postfire regenerated Aleppo pine stand in south-eastern Spain, early thinning was found to increase the initially low CE values (0.14-0.68) and promote a non-clustered tree distribution (Moya et al, 2009). Further research using other thinning methods in MPCF could provide a useful contrast to the results we obtained in tree distribution through random thinning.…”
Section: Discussionmentioning
confidence: 69%
“…According to our findings, this situation was critical in the first months after a fire since plant coverage prevents soil erosion, flooding and runoff [48], while it can significantly affect growth and ecophysiological variables during longer periods [41]. Some morphological or ecophysiological parameters can also vary depending on forest management [49], intraspecific competition (seedling density, spatial distribution, and size of individuals) [50], and seasonality [45].…”
Section: Discussionmentioning
confidence: 85%
“…However, the benefits and risks of thinning to reduce sapling density after a fire are not well-defined. Positive effects of thinning in post-fire regeneration of P. halepensis have been observed for cone production, structural pattern and plant diversity (González-Ochoa et al 2004;De las Heras et al 2007;Moya et al 2009); but negative effects have also been observed after treatment, such as higher levels of defoliation from Pachyrhinus squamosus Kiesenwetter (González-Ochoa et al 2002). Moreover pre-commercial thinning influenced also allometric equations and carbon partitioning in P. halepensis regenerated after fire (De las Heras et al 2012).…”
Section: Introductionmentioning
confidence: 99%